Modulation of DNA binding properties of CCAAT/enhancer binding protein epsilon by heterodimer formation and interactions with NFkappaB pathway - Chumakov, Alexey M. (American Society of Hematology, 2007)
C/EBP epsilon is a transcription factor involved in myeloid cell differentiation. Along with C/EBP-α, -β, -γ, -δ, and -ζ, C/EBP-ϵ belongs to the family of CCAAT/enhancer binding proteins that are implicated in control of growth and differentiation of several cell lineages in inflammation and stress response. We have previously shown that C/EBP-ϵ preferentially binds DNA as a heterodimer with other C/EBP family members such as C/EBP-δ, CHOP (C/EBP-ζ), and the b-zip family protein ATF4. In this study, we define the consensus binding sites for C/EBP-ϵ dimers and C/EBP-ϵ–ATF4 heterodimers. We show that the activated NFkappaB pathway promotes interaction of the C/EBP-ϵ subunit with its cognate DNA binding site via interaction with RelA. RelA-C/EBP interaction is enhanced by phosphorylation of threonine at amino acid 75 and results in increased DNA binding compared with the wild-type nonphosphorylated C/EBP both in vitro and in vivo. We suggest that interaction of the activated NFkappaB pathway and C/EBP-ϵ may be important in selective activation of a subset of C/EBP-ϵ–responsive genes.